O orto-eugenol apresenta atividade antinociceptiva e anti-inflamatória em camundongos - Fonseca, Diogo Vilar da (2016)
Eugenol's ability to reduce nociception and act in the inflammatory process has gained great prominence in the scientific community, emerging interest in researching the ortho-eugenol also has these same activities. Researching ortho-eugenol’s antinociceptive and anti-inflammatory activity, and its possible mechanisms of action is therefore of interest. The administration of vehicle, ortho-eugenol (50, 75 and 100 mg/kg i.p), morphine (10 mg/kg, i.p) or dexamethasone (2 mg/kg, s.c) occurred thirty minutes before the completion of pharmacological tests. The experiments started with psychopharmacological screening and determination of the LD50. The effect of ortho-eugenol on motor coordination in mice was investigated in the rota-rod test. The antinociceptive activity was assessed using chemical tests (test of writhing induced by acetic acid, formalin, test and glutamate) and thermal (hot plate test). To study the role of the adrenergic system, was administered α2-adrenergic antagonist, yohimbine, fifteen minutes before the ortho-eugenol injection the test of writhing induced by acetic acid. The test vascular permeability induced by acetic acid and peritonitis test were used to assess the anti-inflammatory effects of ortho-eugenol in mice. In the test of peritonitis, the levels of pro-inflammatory cytokines and phosphorylated forms of NF-kB and p38 were analyzed in peritoneal fluid. In the behavioral pharmacological screening, the different doses tested ortho-eugenol (200, 225, 250, 300 e 400 mg/kg, i.p.)psicodepressoras showed behavioral changes such as decreased ambulation, and especially analgesia. The LD50 was 307.5 mg / kg, with a confidence interval between 212.1 and 446.0 mg / kg body weight for male and female mice. Pretreatment with ortho-eugenol did not change Rota-rod test coordination test results, but reduced the number of writhes and licking times in the glutamate assay. The reaction time from thermal stimulus was significantly increased in the hot plate test after administration of ortho-eugenol. Treatment with yohimbine reversed the antinociceptive effect of ortho-eugenol, suggesting involvement of the adrenergic system. In anti-inflammatory tests, ortho-eugenol inhibited acetic acid induced vascular permeability and leukocyte migration, reducing TNF-α and IL-1β by virtue of its suppression of NF-kB and p38 phosphorylated forms in the peritonitis test. From these results, ortho-eugenol antinociceptive effects mediated by the adrenergic system and anti-inflammatory activity through regulation of proinflammatory cytokines and phosphorylation of NF-kB and p38 become evident for the first time.